Modified Weekly Cisplatin-Based Chemotherapy Is Acceptable in Postoperative Concurrent Chemoradiotherapy for Locally Advanced Head and Neck Cancer. (17th November 2014) - Lu, Hsueh-Ju; Yang, Chao-Chun; Wang, Ling-Wei; Chu, Pen-Yuan; Tai, Shyh-Kuan; Chen, Ming-Huang; Yang, Muh-Hwa; Chang, Peter Mu-Hsin
Abstract : Background . Triweekly cisplatin-based postoperative concurrent chemoradiotherapy (CCRT) has high intolerance and toxicities in locally advanced head and neck cancer (LAHNC). We evaluated the effect of a modified weekly cisplatin-based chemotherapy in postoperative CCRT. Methods . A total of 117 patients with LAHNC were enrolled between December 2007 and December 2012. Survival, compliance/adverse events, and independent prognostic factors were analyzed. Results . Median follow-up time was 30.0 (3.1–73.0) months. Most patients completed the entire course of postoperative CCRT (radiotherapy ≥ 60 Gy, 94.9%; ≥6 times weekly chemotherapy, 75.2%). Only 17.1% patients required hospital admission. The most common adverse effect was grade 3/4 mucositis (28.2%). No patient died due to protocol-related adverse effects. Multivariate analysis revealed the following independent prognostic factors: oropharyngeal cancer, extracapsular spread, and total radiation dose. Two-year progression-free survival and overall survival rates were 70.9% and 79.5%, respectively. Conclusion . Modified weekly cisplatin-based chemotherapy is an acceptable regimen in postoperative CCRT for LAHNC.